(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
At Cape Tindari, in North-Eastern Sicily, both right-lateral and extensional displacements are documented, but very little is known about the timing of the Upper Pleistocene faults. On the steep cliffs delimiting Cape Tindari, a triangular shaped fissure opens, named Donnavilla Cave, which contains the remains of a continental mammal-bearing deposit plastering the walls of the fissure bored by Lithodomus holes from 73 m up to 85 m a. s. l.. New geological, palaeontological and radiometric data on the Cape Tindari mammal-bearing deposits are here exposed and they are compared with the known terraced mammal bearing deposits in North-eastern Sicily. The mammal-bearing deposits and the walls bored by Lithodomus holes point to the previous existence at Cape Tindari of the inner margin of the MIS 5.5 marine terrace and of the overlying coastal plain deposits. A stalagmite crust previously overlying the mammal-bearing deposits and now hanging and sloping inward into the cave, point to an erosion phase of the inner margin of the coastal plain younger than the stalagmite crust which is 40 ± 4 ka old. At 104 m a.s.l. an older abrasion platform and littoral deposits up to 111 m a.s.l. have been recognised. The two coastal lines and the deeply eroded continental deposits furnish for the first time chronological evidence from stratigraphy and biochronology to time the Late Pleistocene faulting previously recognised at Cape Tindari. They are probably responsible for a lowering of Cape Tindari of about 20 m after the MIS 5.5 substage and for cutting of part of the coastal plain deposits after the deposit of the stalagmite crust.